2002
DOI: 10.1074/jbc.m208920200
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism for Anaerobic Unsaturated Fatty Acid Formation inStreptococcus pneumoniae

Abstract: The anaerobic pathway for unsaturated fatty acid synthesis was established in the 1960s in Escherichia coli. The double bond is introduced into the growing acyl chain by FabA, an enzyme capable of both the dehydration of ␤-hydroxydecanoyl-acyl carrier protein (ACP) to trans-2-decenoyl-ACP, and the isomerization of trans-2 to cis-3-decenoyl-ACP. However, there are a number of anaerobic bacteria whose genomes do not contain a fabA homolog, although these organisms nonetheless produce unsaturated fatty acids. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 48 publications
2
101
0
2
Order By: Relevance
“…It is not clear whether L. bulgaricus would be able to produce unsaturated fatty acids, however, because a FabA or FabM homologue is missing (40). Failure to produce acetyl-CoA or the inability to produce unsaturated fatty acids may explain the need for Tween 80 in laboratory media for L. bulgaricus.…”
Section: Regulatory Functions: Two Siga Homologues and Relatively Fewmentioning
confidence: 97%
“…It is not clear whether L. bulgaricus would be able to produce unsaturated fatty acids, however, because a FabA or FabM homologue is missing (40). Failure to produce acetyl-CoA or the inability to produce unsaturated fatty acids may explain the need for Tween 80 in laboratory media for L. bulgaricus.…”
Section: Regulatory Functions: Two Siga Homologues and Relatively Fewmentioning
confidence: 97%
“…In fact, there is a near reversal of the proportions of saturated and unsaturated membrane fatty acids, with unsaturated fatty acids occupying nearly 60 % of the membrane composition during acidic growth (Fozo & Quivey, 2004;Quivey et al, 2000). Around this time, the fabM gene, encoding an enzyme with trans-2-cis-3-decenoyl isomerase activity, was identified and characterized in Streptococcus pneumoniae (Marrakchi et al, 2002) and shown to be responsible for the formation of unsaturated fatty acids. Parallel studies, conducted with S. mutans, showed that following mutation of the fabM gene, the organism could no longer produce unsaturated fatty acids (Fozo & Quivey, 2004).…”
Section: S Mutans Is the Bacterial Paradigm Of Lactic Acid Bacteria mentioning
confidence: 99%
“…In addition, inactivation of fabM resulted in a substantial reduction in the ability of S. mutans to cause caries in rats (Fozo et al, 2007). This was a departure from the E. coli paradigm of fatty acid synthesis, in which unsaturated fatty acids arise by the combined action of two enzymes, FabA, a dehydratase that forms unsaturated fatty acids from C 10 : hydroxy-fatty acid intermediates and FabB, the condensing enzyme that is capable of elongating unsaturated fatty acids (Marrakchi et al, 2002).…”
Section: S Mutans Is the Bacterial Paradigm Of Lactic Acid Bacteria mentioning
confidence: 99%
“…This can, at least in part, be attributed to the diastereomeric mixture used in the reaction and the formation of E-and Z-isomers. Since the products were inseparable by flash chromatography, the mixture was reacted further in the oxidation of the vinylic borane (18) with Me 3 NO to give aldehyde (19) in 35% yield over two steps (corrected for the dr of 10:3 of alkene (15)). Aldehyde (19) was the only diastereoisomer that was isolated and subsequently reacted in a Pinnick oxidation to give carboxylic acid (20) in 91% yield.…”
Section: Scheme 2 Proposed Mechanism For the Prins Cyclization Of Diementioning
confidence: 99%
“…In contrast to FabZ, FabA is a bifunctional enzyme and also catalyzes the isomerization of trans-2-acetyl-ACP to cis-3-acetyl-ACP, essential for unsaturated fatty acid synthesis. FabA is only present in Gram-negative bacteria and it is believed that Gram-positive bacteria, which also produce unsaturated fatty acids, utilize other isomerases such as FabM and FabZ 1 [18,19]. FabZ is the primary dehydratase in the FAS II pathway and simple inhibitors have been reported that show good in vitro activity for Helicobacter pylori [20].…”
Section: Introductionmentioning
confidence: 99%